PENGARUH LIKUIDITAS, LEVERAGE, AKTIVITAS DAN PROFITABILITAS DALAM MEMPREDIKSI FINANCIAL DISTRESS - Fatmawati, Vivi; Rihardjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to test empirically the influence of liquidity, financial leverage, activity andprofitability to the condition of financial distress. The population in this study are all textile and garmentcompanies listed on the Indonesia Stock Exchange during 2011-2015. Sampling technique used with purposivesampling method so that the research samples obtained as much as 15 companies textile and garment with theamount of data observed as many as 75 observations. Data analysis technique using logistic regression analysismethod. The result of hypothesis testing that Liquidity measured with current ratio has no effect on financialdistress. financial leverage as measured by debt to total asset has a positive effect on financial distress. activitiesmeasured by total asset turnover has a negative effect on financial distress. profitability as measured by returnon asset mapun with return on equity has a negative effect on financial distress.Keywords: liquidity ratio, solvency ratio, activity ratio, profitability ratio, financial distress